Compost and humic substance effects on soil parameters of Vitis vinifera L cv Thompson seedless - Fincheira-Robles, Paola (2016)
The use of organic amendments is common under the concept of integrated nutrient management (INM) in Vitis vinifera (Table grape) to improve plant and soil quality. The objective of this study was to evaluate compost (C) and humic substances (HS) mixed with mineral fertilizer (MF) in an INM program of V. vinifera cv Thompson seedless. The chemical, biochemical and microbiological parameters were evaluated in soil on 1-year- old V. vinifera plants growing on Alfisol soil. Five treatments and control were evaluated: (T1) C+MF, (T2) HS+MF, (T3) C, (T4) HS, (T5) MF and (T6) absolute control. The results indicated that the application of C and HS, increased β glucosidase and dehydrogenase activities, reaching values of 90.2 μg p-nitrophenol g-1h-1 and 9.1 μg de TFP g-124h-1, respectively. In addition, pH was similar in all treatments while electrical conductivity increased with application of mineral and organic amendments, reaching 0.41dS m-1 in T2 (HS+MF). Furthermore, yeast concentration increased with organic amendments or mineral. Correlation analysis indicated significant and positive relationships between PO4-P concentration with MF (0.579) and C (0.431) and nitrogen with MF (0.868). These results support that INM, which combines mineral fertilization and organic amendments, improve positive changes in chemical soil properties and C cycling measured in terms of enzymatic activity in V. vinifera.